Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content 1. The Role of Digital Competencies as a Mediating Variable in the Relationship between Organizational Agility and Achieving Institutional Excellence in Secondary Schools in the Southern Governorates Mr. Mohammed Ibrahim Abu Borhom 2. The Role of School Leadership in Developing Creativity among Teachers of Basic Stage (Public schools in Tubas Province model) Mrs. Rawan Abd Alkareem Alghwanmeh 3. The Effectiveness of an Electronic Training Program Using Collaborative Groups on Developing Teachers’ Teaching Competencies of Health and Physical Education at The Primary Level Mr. Nasser Mohammed Al-Quhaiz , Co-Prof. Rashid Mohammed Al-Jassas , Asst-Prof. Abdulaziz Abdullah Al-Fayez 4. The Effect of an Educational Program Based on Self-Learning to Develop Digital Skills among Al-Aqsa University Students Asst-Prof. Hana Khalil Abu Mutlaq, Co-Prof. Omer Ahmed Ibrahim 5. The effectiveness of the skill of producing mobile applications to enhancing 21st century skills Mrs. Hanan Mohammed Bahkali, Mrs. Saja Saed Al-Jadaani, Co-Prof. Lina Ahmad Al-Farrani 6. Psychological stress and its relationship to social support among tenth and eleventh grade students during the selection of academic subjects in Sultanate of Oman Mrs. Fatma Said Obaid Al-Abri, Prof. Ahmed Maad